Evaluation of agricultural waste material as soil stabilizing agent for soft soil / Muhammad Sofian Abdullah ... [et al.] - Abdullah, Muhammad Sofian; Ibrahim, Anas; Ahmad @ Majid, Mohd Farid; Osman, Muhammad Hafeez; Chow, Shiao Huey (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2009)
The utilization of agricultural waste (agrowaste) material as stabilize agent in lime stabilization provides a satisfactory solution to some of the environmental concerns and problems associated with the agricultural waste management. Recently, agricultural waste such as rice husk ash (RHA) and are used as a lightweight material for building construction especially for the country that produce a lot of agricultural waste. Lack of research in soil stabilization techniques by using agricultural waste lead an idea on conducting this research. This research focusing on investigating the performance of agricultural waste in soil stabilization. The idea of this research is to improve the shear strength of the silty soil (problematic soil) by adding agricultural waste together with hydrated lime as a stabilizing agent. Three types of agricultural waste were selected namely rice husk ash (RHA), palm oil fuel ash (POFA) and sugarcane baggase ash (SCBA). More than hundreds samples were prepared according to the several mix design. The samples were cured for 7, 14, 28 and 60 days and then tested by using unconfined compressive strength (UCT) as a shear strength test. By the result observation, the agricultural waste had increased the shear strength of the silty soil as the percentage of agricultural waste increased at the longer curing time. As a conclusion, this preliminary test shows that the agricultural waste can be used to stabilized the silty soil and hence reduce the environmental problem. Keyword: Agricultural waste, Lime, Silty Soil and UCT.